Evaluation of the Wettability Characteristics of CO2-Brine-Rock-Clay Mineral Systems: Implications for CO2 Sequestration - Fauziah, Cut Aja (Curtin University, 2021)
This research evaluated the wettability characteristics of CO2-brine-rock-clay mineral systems. Wettability is the key physicochemical factor that controls multiphase flow in porous media and influences geological containment security and storage capacities. The study aimed at accurately characterising the wettability of rock and minerals in the presence of CO2 and brine. This work will improve prediction of CO2 storage capacity and containment security, which has important implications for assessing the feasibility of long-term CO2 sequestration projects.